Les documentaires politiques de Robert Greenwald : définir des nouvelles pratiques militantes à l’ère d’Internet - Delphine Letort (Revue LISA)
Robert Greenwald’s emergence as a documentary filmmaker is linked to the political context of George W. Bush’s presidency, marked by a growing discontent caused by the human and financial cost of the unending Iraq war. The success of Outfoxed: Rupert Murdoch’s War on Journalism (2004) prompted Robert Greenwald to found his own company in 2004, Brave New Films, which has allowed him to produce independent documentaries and videos, making use of the Internet for distribution. The films address controversial issues such as the privatization of the Iraq war and the unethical practices of multinational Wal-Mart. Brave New Films relies on its website to promote an alternative informational space, calling for Internet viewers’ collaboration to help broadcast the films and stir up public debates on issues that hardly ever hit the other media headlines.